A repairing method of a high-entropy alloy workpiece

By preparing a high-entropy alloy matrix and using a viscous repair suspension and laser cladding, the problem of micro-defects in high-entropy alloys was solved, improving the material's performance and repair efficiency.

CN117444211BActive Publication Date: 2026-11-06YANCHENG INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311215843.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2026-11-06
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

High-entropy alloys are prone to micro-defects such as microcracks and pores during the preparation process, which leads to a decline in material properties. Existing technologies are unable to effectively repair these defects.

Method used

The matrix was prepared using high-entropy alloy powder with a particle size of 45~105μm. The defects were filled by the penetration of a viscous repair suspension under ultrasonic action and then diffused and solidified in an SPS sintering furnace. Laser surface cladding was then performed to improve the repair quality.

Benefits of technology

It has achieved effective repair of high-entropy alloy matrix, improved the material's hardness, wear resistance and corrosion resistance, enhanced high-temperature performance and interfacial bonding performance, reduced production costs and improved repair efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117444211B_ABST
    Figure CN117444211B_ABST
Patent Text Reader

Abstract

This invention relates to the field of high-entropy alloy materials and discloses a method for repairing high-entropy alloy workpieces. The method includes the steps of preparing the high-entropy alloy workpiece, preparing a viscous repair suspension using nano-sized high-entropy alloy powder and methyl ketone solvent, placing the high-entropy alloy workpiece in the repair suspension to process defects and then sintering and solidifying it to obtain a repaired workpiece, performing defect detection on the repaired workpiece, and performing laser surface cladding on the repaired workpiece. The method of this invention repairs high-entropy alloy workpieces by using a repair suspension to repair surface defects of the high-entropy alloy substrate, filling the defects and uniformly mixing it with the substrate, and then sintering and solidifying it using SPS (Silicon-Pulsed Polymerization), thereby achieving the repair and reinforcement of the high-entropy alloy substrate. Furthermore, laser cladding is used to strengthen and form a dense and uniform coating, significantly improving the surface hardness, wear resistance, and corrosion resistance of the high-entropy alloy workpiece, further enhancing the performance of the high-entropy alloy, and improving the durability and reliability of the workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-entropy alloy materials, and more particularly to a method for repairing high-entropy alloy workpieces. Background Technology

[0002] High-entropy alloys, as a novel type of multi-component alloy material, have attracted widespread attention and research. Due to their unique composition and structure, high-entropy alloys exhibit superior performance in corrosion resistance, high-temperature performance, and mechanical properties. However, due to the complexity of their composition and the requirement for high homogeneity, the preparation process of high-entropy alloys is more complex and difficult than that of traditional alloys. During preparation, some micro-defects inevitably occur, such as original grain boundaries, thermally induced voids, and microcracks. These defects lead to a decline in material properties and affect subsequent processing. Therefore, providing a method for repairing micro-defects on the surface of high-entropy alloy workpieces is of great significance. Summary of the Invention

[0003] Purpose of the invention: The purpose of this invention is to provide a repair method for high-entropy alloy workpieces. By using a repair suspension to fill micro-defects on the surface of the high-entropy alloy workpiece, and by using laser coating to reinforce the micro-defects, the repair quality of high-entropy alloy defects is improved.

[0004] Technical solution: The present invention provides a method for repairing high-entropy alloy workpieces, comprising the following steps: Step S1: Place high-entropy alloy powder with a particle size of 45~105μm in a graphite mold, sinter it in an SPS sintering furnace to prepare a high-entropy alloy matrix, and then machine the high-entropy alloy matrix to obtain a high-entropy alloy workpiece. Step S2: Prepare a viscous repair suspension; Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 10-30 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece. Step S4: Dry the high-entropy alloy workpiece from step S3 and place it in an SPS sintering furnace for diffusion and solidification to obtain the repaired workpiece. Step S5: Perform defect inspection on the repaired workpiece. If it fails, repeat steps S3 and S4 above. Step S6: Perform laser surface cladding on the repaired workpiece to improve the quality of the repair.

[0005] Preferably, in step S1, the sintering temperature is 800~900℃, the sintering pressure is 20~70MPa, the holding time is 5~10min, the heating rate is 10~30℃ / min, and the vacuum degree is 1×10 -3 Pa.

[0006] Preferably, the machining in step S1 is one or a combination of turning, milling, and grinding; the surface roughness of the high-entropy alloy workpiece is ≤ Ra1.6.

[0007] Preferably, the specific preparation steps for preparing the viscous repair suspension in step S2 are as follows: Step S 21 High-entropy alloy powder with a particle size of 80~160nm is mixed evenly with nano-scale grain-forming agent Al2O3 ceramic particles. The amount of nano-Al2O3 ceramic particles added is 1~10wt.% of the mass of high-entropy alloy powder. High-energy ball milling is then performed to obtain nano-scale high-entropy alloy repair powder. Step S 22 Add the nano-sized high-entropy alloy repair powder into the methyl ketone solvent in portions according to the ratio of 10~20g / L. Stir for 10~20min at a stirring speed of 350r / min and a temperature of 30~70℃ to fully mix and form a viscous repair suspension.

[0008] Preferably, step S 21 The specific preparation steps of medium- and nano-sized high-entropy alloy repair powder are as follows: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of (8~15):1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat 2~4 times to ensure a vacuum degree of -0.1MPa during the ball milling process; Step S 212 The ball mill jar is placed on a ball mill and subjected to low-speed, low-energy ball milling by intermittent forward and reverse rotation; the ball milling is performed for 20 to 60 minutes, followed by a 20-minute interval, and then the forward and reverse rotations are alternated for ball milling. The rotation speed of the ball mill is 300 to 350 r / min, and the ball milling time is 5 to 10 hours. Step S 213 The ball mill jar is placed on a ball mill and high-energy ball milling is carried out in an intermittent forward and reverse alternating rotation mode; the ball milling is performed for 30~60 minutes, with a 15-minute interval, and then the forward and reverse alternating ball milling is performed. The rotation speed of the ball mill is 400~600 r / min, and the ball milling time is 50~70 hours. Step S 214 : Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 150~200 r / min, until the ball milled powder is in the form of slurry. Step S216 Place the ball mill jar in a vacuum drying oven at 50~80℃ and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 150~200 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls. Step S 217 The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to grind and break up the agglomerated powder. The high-entropy alloy powder was then placed in an agate grinding jar, and 10-50 nm nano-Al2O3 ceramic particles were added to the agate grinding jar according to the specified ratio. The agate grinding jar was then placed on a ball mill and ball milled using a wet grinding and powder mixing method. Zirconia grinding balls were added at a ball-to-material ratio of (8-15):1, and stearic acid grinding media were added at 1-1.5% of the powder mass. Polyvinyl butyral resin (PVB) was added at 2 wt% of the total high-entropy alloy powder mass. The rotation speed of the ball mill was 150-300 r / min, and the ball milling time was 10-40 h. Step S 218 Place the agate ball milling jar in a vacuum drying oven at 50~80℃ and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 150~200 r / min for 1 hour; take out the ground powder and place it in an agate mortar for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder.

[0009] Preferably, step S1 or step S 211 The medium-to-high entropy alloy powder is AlCoCrFeNi or CoCrFeNiMn alloy powder; The mass percentages of each component in the AlCoCrFeNi alloy powder are: 22.88 wt.% Co, 20.61 wt.% Cr, 22.03 wt.% Fe, 23.37 wt.% Ni, 11.09 wt.% Al, 0.0127 wt.% O, 0.0062 wt.% N, with the balance being unavoidable impurities; The mass percentage of the CoCrFeNiMn high-entropy alloy powder is as follows: 20.50~21.30 wt.% Co, 18.20~18.80 wt.% Cr, 19.50~20.0 wt.% Fe, 20.50~21.30 wt.% Ni, Al≤0.005 wt.% C≤0.008 wt.% N≤0.002 wt.% Si≤0.010 wt.% S≤0.010 wt.% O≤0.08 wt.%, with the balance being unavoidable impurities.

[0010] Preferably, the sintering process in step S4 adopts a melt infiltration process, wherein the sintering temperature is 500~600℃, the pressure is 20~50MPa, the holding time is 1~3min, and the melt infiltration pressure is 0.5~2MPa.

[0011] Preferably, the cladding steps in step S6 are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63 The workpiece surface is preheated, coated with powder, and laser-coated according to a predetermined path. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology of the workpieces, and selecting qualified repaired workpieces.

[0012] Preferably, step S 63 The substrate for laser cladding is preheated to 300℃; the cladding powder is transferred to the nozzle through the central flow channel and sprayed along the scanning path; the laser spot diameter is 80~100μm, the power is 250~400W, the scanning speed is 800~1400mm / s, the line spacing is 0.15~0.20mm, and the sintered layer thickness is 0.03~0.05mm.

[0013] Preferably, the central flow channel of the nozzle is a metal powder flow channel, and the annular flow channel set at 5°~8° with the metal powder flow channel is a protective gas flow channel; wherein, the protective gas is one or a combination of nitrogen, carbon dioxide, and argon; and the cladding powder is TiC or SiC ceramic powder.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The repair method for high-entropy alloy workpieces of the present invention involves using a repair suspension to repair surface defects of a high-entropy alloy matrix prepared by powder metallurgy. This allows the liquid repair agent to fully penetrate into micro-defects such as microcracks and pores within the high-entropy alloy matrix, filling the defects and uniformly mixing with the matrix. The repair agent is then sintered and solidified via SPS (Silicone Polymerization), thereby achieving the repair and reinforcement of the high-entropy alloy matrix. The repair suspension allows for controllable repair temperature and pressure to meet the repair requirements of different defects, ensuring sufficient bonding and diffusion of the repair suspension, enabling the repair agent to form a dense structure in the defect area. This repair method is suitable for high-entropy alloy matrices of various shapes and sizes, is not limited by the complex morphology of the matrix, and the suspension repair is easy to implement, helping to reduce production costs and improve repair efficiency. 2. After completing the suspension repair on the surface of the high-entropy alloy workpiece, laser cladding is used to strengthen and form a dense and uniform coating, which significantly improves the surface hardness, wear resistance and corrosion resistance of the high-entropy alloy workpiece, further enhancing the performance of the high-entropy alloy, so that it still has excellent performance under high temperature conditions. At the same time, it improves the interfacial bonding performance of the material and improves the durability and reliability of the workpiece. Attached Figure Description

[0015] Figure 1 This is a schematic flowchart of the high-entropy alloy matrix repair method of the present invention; Figure 2 for Figure 1 Schematic diagram of the specific process for repairing medium- and high-entropy alloy substrates; Figure 3 SEM images of high-entropy alloy workpieces ((a) 50 μm; (b) 20 μm; (c) 10 μm); Figure 4 SEM images of the repaired workpiece ((a) 20 μm; (b) 10 μm); Figure 5 Backscattered SEM image of a high-entropy alloy workpiece; Figure 6 Backscattered SEM image of the repaired high-entropy alloy workpiece; Figure 7 XRD patterns of the high-entropy alloy workpiece before and after repair; Figure 8 EBSD IPF images of the high-entropy alloy before and after restoration; Figure 9 The orientation angle distribution diagrams of the high-entropy alloy workpiece before and after repair are shown in ((a) high-entropy alloy workpiece, (b) cladding processing area). Figure 10 The particle size distribution diagrams of the high-entropy alloy workpiece before and after repair are shown in ((a) high-entropy alloy workpiece, (b) workpiece product). Figure 11 EBSD-PF images of high-entropy alloy workpieces before and after restoration ((a) high-entropy alloy workpiece, (b) workpiece product); Figure 12 TEM images of the cladding area of ​​the workpiece after laser cladding ((a) misalignment structure, (b) local twin structure); Figure 13 The images show TEM images of the cladding area and corresponding electron diffraction images of the workpiece after laser cladding. Detailed Implementation

[0016] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the following will be described in conjunction with the accompanying drawings. Figures 1-13The technical solutions of the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. All other embodiments obtained by those skilled in the art based on the described embodiments of the present invention are within the scope of protection of the present invention.

[0017] like Figures 1-2 As shown, a method for repairing high-entropy alloy workpieces according to the present invention includes the following steps: Step S1: Place high-entropy alloy powder with a particle size of 45~105μm into a graphite mold, and sinter it in an SPS sintering furnace at a sintering temperature of 800~900℃, a sintering pressure of 20~70MPa, and a vacuum degree of 1×10⁻⁶. -3 A high-entropy alloy matrix is ​​prepared by sintering under the conditions of Pa, heating rate of 10-30℃ / min, and holding time of 5-10min. Then, the high-entropy alloy matrix is ​​processed by one or a combination of turning, milling, and grinding to obtain a high-entropy alloy workpiece with a surface roughness ≤ Ra1.6.

[0018] Step S2: The specific steps for preparing the viscous repair suspension are as follows: Step S 21 High-entropy alloy powder with a particle size of 80-160 nm is mixed uniformly with Al2O3 ceramic particles, a nano-grain-forming agent. The amount of Al2O3 ceramic particles added is 1-10 wt.% of the mass of the high-entropy alloy powder. High-energy ball milling is then performed to obtain nano-sized high-entropy alloy repair powder. The specific preparation steps are as follows: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of (8~15):1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat 2~4 times to ensure a vacuum degree of -0.1MPa during the ball milling process; Step S 212 The ball mill jar is placed on a ball mill and subjected to low-speed, low-energy ball milling by intermittent forward and reverse rotation; the ball milling is performed for 20 to 60 minutes, followed by a 20-minute interval, and then the forward and reverse rotations are alternated for ball milling. The rotation speed of the ball mill is 300 to 350 r / min, and the ball milling time is 5 to 10 hours. Step S 213 The ball mill jar is placed on a ball mill and high-energy ball milling is carried out in an intermittent forward and reverse alternating rotation mode; the ball milling is performed for 30~60 minutes, with a 15-minute interval, and then the forward and reverse alternating ball milling is performed. The rotation speed of the ball mill is 400~600 r / min, and the ball milling time is 50~70 hours. Step S 214: Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 150~200 r / min, until the ball milled powder is in the form of slurry. Step S 216 Place the ball mill jar in a vacuum drying oven at 50~80℃ and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 150~200 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls. Step S 217 The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to grind and break up the agglomerated powder. The high-entropy alloy powder was then placed in an agate grinding jar, and 10-50 nm nano-Al2O3 ceramic particles were added to the agate grinding jar according to the specified ratio. The agate grinding jar was then placed on a ball mill and ball milled using a wet grinding and powder mixing method. Zirconia grinding balls were added at a ball-to-material ratio of (8-15):1, and stearic acid grinding media were added at 1-1.5% of the powder mass. Polyvinyl butyral resin (PVB) was added at 2 wt% of the total high-entropy alloy powder mass. The rotation speed of the ball mill was 150-300 r / min, and the ball milling time was 10-40 h. Step S 218 Place the agate ball milling jar in a vacuum drying oven at 50~80℃ and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 150~200 r / min for 1 hour; take out the ground powder and place it in an agate round bowl for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder. Step S 22 Add the nano-sized high-entropy alloy repair powder into the methyl ketone solvent in portions according to the ratio of 10~20g / L. Stir for 10~20min at a stirring speed of 350r / min and a temperature of 30~70℃ to fully mix and form a viscous repair suspension.

[0019] Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 10-30 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece.

[0020] Step S4: Remove the high-entropy alloy workpiece from the self-repair suspension, dry it to remove methyl ketone from the workpiece surface, and then place the dried workpiece in an SPS sintering furnace and use the melt infiltration method to diffuse and solidify under the conditions of sintering temperature of 500~600℃, pressure of 20~50MPa, melt infiltration pressure of 0.5~2MPa, and holding time of 1~3min to obtain the repaired workpiece.

[0021] Step S5: Perform defect inspection on the repaired workpiece. If it fails to meet the requirements, repeat the above process of soaking in the repair suspension and solidification sintering to ensure the repair quality of the workpiece.

[0022] Step S6: Perform laser surface cladding on the repaired workpiece. The specific steps are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63 The laser cladding equipment preheats the workpiece surface to 300℃ using a substrate. Cladding powder is transferred to the nozzle through a central channel and sprayed along the scanning path. The central channel of the nozzle is a metal powder channel, and an annular channel at a 5°~8° angle to the metal powder channel serves as a protective gas channel. The protective gas is one or a combination of nitrogen, carbon dioxide, and argon. The cladding powder is TiC or SiC ceramic powder. Laser heating cladding is performed on the workpiece surface according to a predetermined path. The laser spot diameter is 80~100μm, the power is 250~400W, the scanning speed is 800~1400mm / s, the line spacing is 0.15~0.20mm, and the sintered layer thickness after cladding is 0.03~0.05mm. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology, and selecting qualified repaired workpieces. The standard for qualified finished workpieces is that the product surface is smooth and free from defects such as cracks and holes.

[0023] The high-entropy alloy powder used in the preparation of the high-entropy alloy matrix and the preparation of the nanoscale high-entropy alloy repair powder is AlCoCrFeNi or CoCrFeNiMn alloy powder; the mass percentages of each component in the AlCoCrFeNi alloy powder are: 22.88 wt.% Co, 20.61 wt.% Cr, 22.03 wt.% Fe, 23.37 wt.% Ni, 11.09 wt.% Al, 0.0127 wt.% O, 0.0062 The mass percentages of the CoCrFeNiMn high-entropy alloy powder are: 20.50~21.30 wt.% Co, 18.20~18.80 wt.% Cr, 19.50~20.0 wt.% Fe, 20.50~21.30 wt.% Ni, Al≤0.005 wt.% C≤0.008 wt.% N≤0.002 wt.% Si≤0.010 wt.% S≤0.010 wt.% O≤0.08 wt.%, with the balance being unavoidable impurities. Example 1:

[0024] The present invention provides a method for repairing high-entropy alloy workpieces, comprising the following steps: Step S1: Place AlCoCrFeNi high-entropy alloy powder with a particle size of 45~105μm into a graphite mold, and sinter in an SPS furnace at a sintering temperature of 900℃, a sintering pressure of 50 MPa, and a vacuum degree of 1×10⁻⁶. -3 A high-entropy alloy matrix is ​​prepared by sintering under the conditions of Pa, heating rate of 30℃ / min, and holding time of 10min. Then, the high-entropy alloy matrix is ​​processed by one or a combination of turning, milling, and grinding to obtain a high-entropy alloy workpiece with a surface roughness ≤ Ra1.6.

[0025] Step S2: The specific steps for preparing the viscous repair suspension are as follows: Step S 21 AlCoCrFeNi high-entropy alloy powder with a particle size of 80~160nm was mixed uniformly with Al2O3 ceramic particles, a nano-grain-forming agent. The amount of Al2O3 ceramic particles added was 2wt.% of the mass of the high-entropy alloy powder. High-energy ball milling was then performed to obtain nano-sized high-entropy alloy repair powder. The specific preparation steps are as follows: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of 8:1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat 4 times to ensure a vacuum degree of -0.1MPa during the ball milling process; Step S 212The ball mill jar was placed on a ball mill and subjected to low-speed, low-energy ball milling using intermittent forward and reverse rotation. The ball milling process lasted 60 minutes, followed by a 20-minute interval, and then alternating forward and reverse rotations. The ball mill rotated at 300 r / min for 10 hours. Step S 213 The ball mill jar was placed on a ball mill and high-energy ball milling was carried out using an intermittent forward and reverse alternating rotation mode; the ball milling was performed for 30 minutes, followed by a 15-minute interval, and then the forward and reverse alternating rotation was used for ball milling. The rotation speed of the ball mill was 400 r / min, and the ball milling time was 50 h. Step S 214 : Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 150 r / min, until the ball milled powder is in the form of a slurry. Step S 216 Place the ball mill jar in a vacuum drying oven at 50°C and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 150 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls by impact. Step S 217 The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to fully grind and break up the agglomerated powder. The high-entropy alloy powder was then placed in an agate grinding jar, and 10-50nm nano-Al2O3 ceramic particles were added to the agate grinding jar according to the specified ratio. The agate grinding jar was then placed on a ball mill and ball milled using a wet grinding and powder mixing method. Zirconia grinding balls were added at a ball-to-powder ratio of 8:1, stearic acid grinding media were added at 1% of the powder mass, and polyvinyl butyral resin (PVB) was added at 2wt% of the total high-entropy alloy powder mass. The ball mill rotation speed was 200r / min, and the ball milling time was 20h. Step S 218 Place the agate ball mill jar in a vacuum drying oven at 50℃ and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 150 r / min for 1 hour; take out the ground powder and place it in an agate round bowl for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder. Step S 22 The nano-sized high-entropy alloy repair powder was added to the methyl ketone solvent in portions according to the ratio of 10g / L. The mixture was stirred for 10 minutes at a stirring speed of 350r / min and a temperature of 30℃ to form a viscous repair suspension.

[0026] Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 10 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece.

[0027] Step S4: Remove the high-entropy alloy workpiece from the self-repair suspension, dry it to remove the methyl ketone from the surface of the workpiece, and then place the dried workpiece in an SPS sintering furnace and use the melt infiltration method to diffuse and solidify under the conditions of sintering temperature of 600℃, pressure of 50MPa, melt infiltration pressure of 2MPa, and holding time of 3min to obtain the repaired workpiece.

[0028] Step S5: Perform defect inspection on the repaired workpiece. If it fails to meet the requirements, repeat the above process of soaking in the repair suspension and solidification sintering to ensure the repair quality of the workpiece.

[0029] Step S6: Perform laser surface cladding on the repaired workpiece. The specific steps are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63 The laser cladding equipment preheats the workpiece surface on its substrate to 300℃. Cladding powder is transferred to the nozzle through a central channel and sprayed along the scanning path. The central channel of the nozzle is a metal powder channel, and the annular channel at a 7° angle to the metal powder channel is a protective gas channel. The protective gas is one or a combination of nitrogen, carbon dioxide, and argon. The cladding powder is TiC or SiC ceramic powder. Laser heating cladding is performed on the workpiece surface according to a predetermined path. The laser spot diameter is 100μm, the power is 400W, the scanning speed is 1400mm / s, the line spacing is 0.20mm, and the sintered layer thickness after cladding is 0.05mm. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology, and selecting qualified repaired workpieces. The standard for qualified finished workpieces is that the product surface is smooth and free from defects such as cracks and holes. Example 2:

[0030] like Figures 1-2 As shown, a method for repairing high-entropy alloy workpieces according to the present invention includes the following steps: Step S1: Place CoCrFeNiMn high-entropy alloy powder with a particle size of 45~105μm into a graphite mold, and sinter in an SPS furnace at a sintering temperature of 800℃, a sintering pressure of 50MPa, and a vacuum degree of 1×10⁻⁶. -3A high-entropy alloy matrix is ​​prepared by sintering under the conditions of Pa, heating rate of 20℃ / min, and holding time of 5min. Then, the high-entropy alloy matrix is ​​processed by one or a combination of turning, milling, and grinding to obtain a high-entropy alloy workpiece with a surface roughness ≤ Ra1.6.

[0031] Step S2: The specific steps for preparing the viscous repair suspension are as follows: Step S 21 High-entropy alloy powder of CoCrFeNiMn with a particle size of 80~160nm was mixed uniformly with nano-sized grain-forming agent Al2O3 ceramic particles, the amount of nano-Al2O3 ceramic particles added being 2wt.% of the mass of the high-entropy alloy powder; high-energy ball milling was then performed to obtain nano-sized high-entropy alloy repair powder. The specific preparation steps are as follows: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of 8:1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat 4 times to ensure a vacuum degree of -0.1MPa during the ball milling process; Step S 212 The ball mill jar was placed on a ball mill and subjected to low-speed, low-energy ball milling using intermittent forward and reverse rotation. The ball milling process lasted 30 minutes, followed by a 20-minute interval, and then alternating forward and reverse rotations. The ball mill rotated at 300 r / min for 5 hours. Step S 213 The ball mill jar was placed on a ball mill and high-energy ball milling was carried out using an intermittent forward and reverse alternating rotation mode; the ball milling was performed for 30 minutes, followed by a 15-minute interval, and then the forward and reverse alternating rotation was used for ball milling. The rotation speed of the ball mill was 400 r / min, and the ball milling time was 50 h. Step S 214 : Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 150 r / min, until the ball milled powder is in the form of a slurry. Step S 216 Place the ball mill jar in a vacuum drying oven at 80℃ and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 150 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls. Step S 217The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to fully grind and break up the agglomerated powder. The high-entropy alloy powder was then placed in an agate grinding jar, and 10-50nm nano-Al2O3 ceramic particles were added to the agate grinding jar according to the specified ratio. The agate grinding jar was placed on a ball mill and ball milled using the wet grinding and powder mixing method. Zirconia grinding balls were added at a ball-to-powder ratio of 15:1, stearic acid grinding media were added at 1.5% of the powder mass, and polyvinyl butyral resin (PVB) was added at 2wt% of the total high-entropy alloy powder mass. The ball mill rotation speed was 200 r / min, and the ball milling time was 40 h. Step S 218 Place the agate ball mill jar in an 80℃ vacuum drying oven and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 200 r / min for 1 hour; take out the ground powder and place it in an agate round bowl for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder. Step S 22 The nano-sized high-entropy alloy repair powder was added to the methyl ketone solvent in portions at a ratio of 20 g / L. The mixture was stirred for 10 minutes at a stirring speed of 350 r / min and a temperature of 50℃ to form a viscous repair suspension.

[0032] Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 10 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece.

[0033] Step S4: Remove the high-entropy alloy workpiece from the self-repair suspension, dry it to remove the methyl ketone from the surface of the workpiece, and then place the dried workpiece in an SPS sintering furnace and use the melt infiltration method to diffuse and solidify under the conditions of sintering temperature of 500℃, pressure of 30MPa, melt infiltration pressure of 2MPa, and holding time of 3min to obtain the repaired workpiece.

[0034] Step S5: Perform defect inspection on the repaired workpiece. If it fails to meet the requirements, repeat the above process of soaking in the repair suspension and solidification sintering to ensure the repair quality of the workpiece.

[0035] Step S6: Perform laser surface cladding on the repaired workpiece. The specific steps are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63The laser cladding equipment preheats the workpiece surface on its substrate to 300°C. Cladding powder is transferred to the nozzle through a central channel and sprayed along the scanning path. The central channel of the nozzle is a metal powder channel, and the annular channel at a 7° angle to the metal powder channel is a protective gas channel. The protective gas is one or a combination of nitrogen, carbon dioxide, and argon. The cladding powder is TiC or SiC ceramic powder. Laser heating cladding is performed on the workpiece surface according to a predetermined path. The laser spot diameter is 80μm, the power is 400W, the scanning speed is 800mm / s, the line spacing is 0.15mm, and the sintered layer thickness after cladding is 0.03mm. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology, and selecting qualified repaired workpieces. The standard for qualified finished workpieces is that the product surface is smooth and free from defects such as cracks and holes. Example 3:

[0036] like Figures 1-2 As shown, a method for repairing high-entropy alloy workpieces according to the present invention includes the following steps: Step S1: Place AlCoCrFeNi high-entropy alloy powder with a particle size of 45~105μm into a graphite mold, and sinter in an SPS furnace at a sintering temperature of 850℃, a sintering pressure of 40MPa, and a vacuum degree of 1×10⁻⁶. -3 A high-entropy alloy matrix is ​​prepared by sintering under the conditions of Pa, heating rate of 20℃ / min, and holding time of 10min. Then, the high-entropy alloy matrix is ​​processed by one or a combination of turning, milling, and grinding to obtain a high-entropy alloy workpiece with a surface roughness ≤Ra1.6.

[0037] Step S2: The specific steps for preparing the viscous repair suspension are as follows: Step S 21 High-entropy alloy powder of CoCrFeNiMn with a particle size of 80~160nm was mixed uniformly with nano-sized grain-forming agent Al2O3 ceramic particles. The amount of nano-Al2O3 ceramic particles added was 1wt.% of the mass of the high-entropy alloy powder. High-energy ball milling was then performed to obtain nano-sized high-entropy alloy repair powder. The specific preparation steps are as follows: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of 10:1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat twice to ensure a vacuum of -0.1MPa during the ball milling process; Step S 212The ball mill jar was placed on a ball mill and subjected to low-speed, low-energy ball milling using intermittent forward and reverse rotation. The ball milling process lasted 30 minutes, followed by a 20-minute interval, and then alternating forward and reverse rotations. The ball mill rotated at 300 r / min for 10 hours. Step S 213 The ball mill jar was placed on a ball mill and high-energy ball milling was carried out using an intermittent forward and reverse alternating rotation mode; the ball milling was performed for 60 minutes, followed by a 15-minute interval, and then the forward and reverse alternating rotation was used for ball milling. The rotation speed of the ball mill was 600 r / min, and the ball milling time was 50 hours. Step S 214 : Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 200 r / min, until the ball milled powder is in the form of a slurry. Step S 216 Place the ball mill jar in a vacuum drying oven at 50°C and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 200 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls by impact. Step S 217 The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to fully grind and break up the agglomerated powder. The high-entropy alloy powder was then placed in an agate grinding jar, and 10-50nm nano-Al2O3 ceramic particles were added to the agate grinding jar according to the specified ratio. The agate grinding jar was placed on a ball mill and ball milled using a wet grinding and powder mixing method. Zirconia grinding balls were added at a ball-to-powder ratio of 12:1, and stearic acid grinding media were added at 1.2% of the powder mass, while polyvinyl butyral resin (PVB) was added at 2wt% of the total high-entropy alloy powder mass. The ball mill rotation speed was 200 r / min, and the ball milling time was 30 h. Step S 218 Place the agate ball mill jar in a vacuum drying oven at 60℃ and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 200 r / min for 1 hour; take out the ground powder and place it in an agate round bowl for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder. Step S 22 The nano-sized high-entropy alloy repair powder was added to the methyl ketone solvent in portions at a ratio of 15 g / L. The mixture was stirred for 20 minutes at a stirring speed of 350 r / min and a temperature of 50℃ to form a viscous repair suspension.

[0038] Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 30 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece.

[0039] Step S4: Remove the high-entropy alloy workpiece from the self-repair suspension, dry it to remove the methyl ketone from the surface of the workpiece, and then place the dried workpiece in an SPS sintering furnace and use the melt infiltration method to diffuse and solidify under the conditions of sintering temperature of 600℃, pressure of 50MPa, melt infiltration pressure of 2MPa, and holding time of 3min to obtain the repaired workpiece.

[0040] Step S5: Perform defect inspection on the repaired workpiece. If it fails to meet the requirements, repeat the above process of soaking in the repair suspension and solidification sintering to ensure the repair quality of the workpiece.

[0041] Step S6: Perform laser surface cladding on the repaired workpiece. The specific steps are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63 The laser cladding equipment preheats the workpiece surface on its substrate to 300°C. Cladding powder is transferred to the nozzle through a central flow channel and sprayed along the scanning path. The central flow channel of the nozzle is a metal powder flow channel, and the annular flow channel at a 7° angle to the metal powder flow channel is a protective gas flow channel. The protective gas is one or a combination of nitrogen, carbon dioxide, and argon. The cladding powder is TiC or SiC ceramic powder. Laser heating cladding is performed on the cladding powder on the workpiece surface according to a predetermined path. The laser spot diameter is 80μm, the power is 300W, the scanning speed is 1000mm / s, the line spacing is 0.20mm, and the sintered layer thickness after cladding is 0.04mm. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology, and selecting qualified repaired workpieces. The standard for qualified finished workpieces is that the product surface is smooth and free from defects such as cracks and holes. Example 4:

[0042] like Figures 1-2 As shown, a method for repairing high-entropy alloy workpieces according to the present invention includes the following steps: Step S1: Place CoCrFeNiMn high-entropy alloy powder with a particle size of 45~105μm into a graphite mold, and sinter in an SPS furnace at a sintering temperature of 800℃, a sintering pressure of 50MPa, and a vacuum degree of 1×10⁻⁶. -3A high-entropy alloy matrix is ​​prepared by sintering under the conditions of Pa, heating rate of 20℃ / min, and holding time of 8min. Then, the high-entropy alloy matrix is ​​processed by one or a combination of turning, milling, and grinding to obtain a high-entropy alloy workpiece with a surface roughness ≤ Ra1.6.

[0043] Step S2: The specific steps for preparing the viscous repair suspension are as follows: Step S 21 AlCoCrFeNi high-entropy alloy powder with a particle size of 80~160nm was mixed uniformly with Al2O3 ceramic particles, a nano-grain-forming agent. The amount of Al2O3 ceramic particles added was 4.0 wt.% of the mass of the high-entropy alloy powder. High-energy ball milling was then performed to obtain nano-sized high-entropy alloy repair powder. The specific preparation steps are as follows: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of 12:1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat 3 times to ensure a vacuum degree of -0.1MPa during the ball milling process; Step S 212 The ball mill jar was placed on a ball mill and subjected to low-speed, low-energy ball milling using intermittent forward and reverse rotation. The ball milling process lasted 30 minutes, followed by a 20-minute interval, and then alternating forward and reverse rotations. The ball mill rotated at 300 r / min for 10 hours. Step S 213 The ball mill jar was placed on a ball mill and high-energy ball milling was carried out using an intermittent forward and reverse alternating rotation mode; the ball milling was performed for 30 minutes, followed by a 15-minute interval, and then the forward and reverse alternating rotation was used for ball milling. The rotation speed of the ball mill was 400 r / min, and the ball milling time was 50 h. Step S 214 : Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 150 r / min, until the ball milled powder is in the form of a slurry. Step S 216 Place the ball mill jar in a vacuum drying oven at 50°C and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 150 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls by impact. Step S 217The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to fully grind and break up the agglomerated powder. The high-entropy alloy powder was then placed in an agate grinding jar, and 10-50nm nano-Al2O3 ceramic particles were added to the agate grinding jar according to the specified ratio. The agate grinding jar was placed on a ball mill and ball milled using the wet grinding and powder mixing method. Zirconia grinding balls were added at a ball-to-powder ratio of 10:1, stearic acid grinding media were added at 1.2% of the powder mass, and polyvinyl butyral resin (PVB) was added at 2wt% of the total high-entropy alloy powder mass. The ball mill rotation speed was 150r / min, and the ball milling time was 20h. Step S 218 Place the agate ball mill jar in a vacuum drying oven at 65℃ and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 150 r / min for 1 hour; take out the ground powder and place it in an agate round bowl for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder. Step S 22 The nano-sized high-entropy alloy repair powder was added to the methyl ketone solvent in portions at a ratio of 10 g / L. The mixture was stirred for 10 minutes at a stirring speed of 350 r / min and a temperature of 50℃ to form a viscous repair suspension.

[0044] Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 20 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece.

[0045] Step S4: Remove the high-entropy alloy workpiece from the self-repair suspension, dry it to remove the methyl ketone from the surface of the workpiece, and then place the dried workpiece in an SPS sintering furnace and use the melt infiltration method to diffuse and solidify under the conditions of sintering temperature of 600℃, pressure of 50MPa, melt infiltration pressure of 2MPa, and holding time of 3min to obtain the repaired workpiece.

[0046] Step S5: Perform defect inspection on the repaired workpiece. If it fails to meet the requirements, repeat the above process of soaking in the repair suspension and solidification sintering to ensure the repair quality of the workpiece.

[0047] Step S6: Perform laser surface cladding on the repaired workpiece. The specific steps are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63The laser cladding equipment preheats the workpiece surface on its substrate to 300°C. Cladding powder is transferred to the nozzle through a central channel and sprayed along the scanning path. The central channel of the nozzle is a metal powder channel, and the annular channel at a 7° angle to the metal powder channel is a protective gas channel. The protective gas is one or a combination of nitrogen, carbon dioxide, and argon. The cladding powder is TiC or SiC ceramic powder. Laser heating cladding is performed on the workpiece surface according to a predetermined path. The laser spot diameter is 80μm, the power is 400W, the scanning speed is 800mm / s, the line spacing is 0.15mm, and the sintered layer thickness after cladding is 0.03mm. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology, and selecting qualified repaired workpieces. The standard for qualified finished workpieces is that the product surface is smooth and free from defects such as cracks and holes.

[0048] The repair process for the high-entropy alloy workpiece of this invention is as follows: Figure 1 and Figure 2 As shown, taking the repair process of the high-entropy alloy workpiece prepared by AlCoCrFeNi high-entropy alloy powder in Example 1 as an example, the physicochemical properties of the high-entropy alloy workpiece and the repaired workpiece product were characterized, and the results are as follows: Figure 3 SEM images of high-entropy alloy workpieces ((a) 50 μm; (b) 20 μm; (c) 10 μm). Figure 4 SEM images of the repaired workpiece ((a) 20 μm; (b) 10 μm). Figure 3 and Figure 4 The comparison shows that in high-entropy alloy workpieces prepared by powder metallurgy, the components of the high-entropy alloy powder are not fully fused, resulting in a large number of defects such as microcracks and pores in the microscopic state. After repair and laser cladding, the defects on the surface of the finished workpiece are well repaired, and the defects are significantly reduced.

[0049] Figure 5 Backscattered SEM images of high-entropy alloy workpieces. Figure 6 This is a backscattered SEM image of the repaired high-entropy alloy workpiece. (Source: [Original Text]) Figure 5 It can be seen that the powder melting of high-entropy alloy workpieces prepared by powder metallurgy is incomplete, and the components are irregularly distributed and aggregated. The main reason is the structural defects introduced by the sintering powder metallurgy process; Figure 6 It can be seen that repairing with a suspension and laser cladding significantly repaired the surface defects of high-entropy alloy workpieces, and the constituent elements in the cladding zone showed a uniform distribution. Figures 3-4 As shown, the repair method of the present invention can effectively repair microscopic defects in high-entropy alloy workpieces.

[0050] Figure 7 The images show the XRD patterns of the high-entropy alloy workpiece before and after repair. After repair, the phase composition of the high-entropy alloy workpiece in the cladding zone is a single BCC solid solution structure (Fe-Cr rich BCC phase) similar to the matrix. During the cladding process of the high-entropy alloy workpiece, each component melts first and then crystallizes, resulting in a higher peak value of the BCC phase. In addition, the presence of Al element will increase the BCC phase during the cladding process. After the Al element decreases after cladding, a small amount of FCC phase (Fe-Cr rich FCC phase) may precipitate.

[0051] Figure 8 For the EBSD-IPF images of the high-entropy alloy before and after restoration, by Figure 8 (a) It can be seen that the high-entropy alloy workpiece before repair exhibits a matrix structure with obvious coarse grains and numerous voids. Figure 8 (b) It can be seen that the grains gradually become finer along the BD direction, and a heat-affected zone appears, forming as shown in the figure. Figure 8 In (c) / (d), the microstructure of the cladding zone with its compact structure and fine grains is significantly improved compared to the microstructure of the high-entropy alloy workpiece before repair.

[0052] Figure 9 The orientation angle distribution diagrams of the high-entropy alloy workpiece before and after repair are shown in ((a) high-entropy alloy workpiece, (b) cladding area). Figure 9 (a) / (b) shows that the low-angle grain boundaries (LAGBs) with orientation angles between 2° and 5° are significantly increased after laser cladding. The proportion of LABs in the laser-clad area of ​​the repaired workpiece is nearly 30% higher than that of the high-entropy alloy workpiece, indicating that more dislocations occurred during the laser cladding process. Compared with ordinary alloys, high-entropy alloys have more dislocations and are more prone to dislocation slip. This phenomenon leads to an increase in the metal plasticity of the alloy. Laser cladding can significantly increase the dislocation ratio. The increased dislocation ratio of the finished workpiece will cause the dislocations to pin and entangle with each other, thereby effectively preventing dislocation slip and improving the strength of the workpiece.

[0053] Figure 10 The image shows the particle size distribution of a high-entropy alloy workpiece before and after repair ((a) high-entropy alloy workpiece, (b) workpiece product). Figure 9 It is known that the grains in the laser cladding processing area are finer, and the grain size of the laser cladding processing area is reduced by 2.4% compared to the high entropy alloy workpiece. This result depends on the cooling rate. Laser cladding processing makes the workpiece cool faster. According to research, the increase in cooling rate will make the grain structure finer. Therefore, the microstructure of the workpiece becomes dense and uniform after laser cladding processing.

[0054] Figure 11 To restore the EBSD-PF images of the high-entropy alloy workpiece before and after restoration ((a) high-entropy alloy workpiece, (b) workpiece product), by Figure 11 It is known that the maximum polarity density of the high-entropy alloy workpiece prepared by powder metallurgy is 4.259. After laser cladding, the maximum polarity density of the workpiece increases to 6.581. The increase in polarity density indicates an increase in strong crystal texture, that is, both the number and structure of grains are improved, resulting in stronger metallic properties and more obvious anisotropy of the workpiece. According to the grain growth trend and its changes, it can be seen that the microstructure of the laser cladding area is closely related to the temperature field distribution during the laser cladding process. The solidification structure will also change accordingly according to the changes in temperature gradient and distribution. With the change of crystal orientation, it will grow towards the BD direction, i.e., the 001 direction, which also proves the important role of heat flux in the grain growth process.

[0055] Figure 12 TEM images of the cladding area of ​​the workpiece after laser cladding ((a) misalignment structure, (b) local twinning structure), by Figure 12 (a) It can be seen that many dislocations and stacking faults appear in the cladding area of ​​the workpiece. This is due to the severe plastic deformation and slip that occur during the laser cladding process of high-entropy alloy workpieces. The increase in dislocations can enhance the anisotropy of the alloy workpiece. At the same time, a clear twinned structure can be observed. Figure 12 (b) is an image of a local twinned structure. In this local twinned structure, the two crystals form a mirror-symmetric phase relationship along a common crystal plane. The twin plane can also be clearly observed in the image. The formation of twins changes the orientation of the crystals. This change causes regions that were not prone to slip to become prone to slip, thereby further stimulating slip and crystal deformation. Under the interaction of structures such as twins and dislocations formed by slip, the metallic properties of the cladding zone are greatly improved. The fast cooling rate during laser cladding processing generates large thermal stress between the cladding and uncladding areas of the workpiece. The formation of this thermal stress also accelerates the plastic deformation of the alloy, thereby generating slip and forming more dislocations.

[0056] Figure 13 TEM images of the cladding area and corresponding electron diffraction images of the workpiece after laser cladding. Figure 13 In (a), an elliptical micron-sized dispersed phase was observed at the top of the image. High-resolution electron diffraction patterns revealed this phase to be the B2 phase, with a BCC phase detected in the surrounding area. This indicates that the cladding zone is primarily composed of a solid-solution BCC structure based on the B2 phase, and the properties of this structure mainly depend on the abundant lattice site coordination between the B2 and BCC phases. Furthermore, the combination of these phases also optimizes the metallic properties of the alloy. In addition, from... Figure 12 (b) shows the FCC phase distributed in a dendritic form in the BCC phase below the image. This conclusion reveals that the strengthening of high-entropy alloy repair workpieces by laser cladding is the result of the synergistic effect of multiple strengthening mechanisms such as dislocation strengthening, solid solution strengthening, and twinning strengthening.

[0057] The above are preferred embodiments of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for repairing high-entropy alloy workpieces, characterized in that, Includes the following steps: Step S1: Place high-entropy alloy powder with a particle size of 45~105μm in a graphite mold, sinter it in an SPS sintering furnace to prepare a high-entropy alloy matrix, and then machine the high-entropy alloy matrix to obtain a high-entropy alloy workpiece. Step S2: Prepare a viscous repair suspension. The specific preparation steps are as follows: Step S 21 : high-entropy alloy powder with a particle size of 80-160 nm is mixed with nano-sized grain generator Al2O3 ceramic particles uniformly, the addition amount of nano Al2O3 ceramic particles is 1-10 wt.% of the mass of the high-entropy alloy powder; high-energy ball milling treatment is carried out to obtain nano-sized high-entropy alloy repair powder, and the specific preparation steps are: Step S 211 Dry and weigh the high-entropy alloy powder, add it to the ball mill jar, add cemented carbide grinding balls at a ball-to-material ratio of (8~15):1, and add industrial anhydrous ethanol and stearic acid mixed process control agent; evacuate the ball mill jar and then fill it with argon or nitrogen, repeat 2~4 times to ensure a vacuum degree of -0.1MPa during the ball milling process; Step S 212 The ball mill jar is placed on a ball mill and subjected to low-speed, low-energy ball milling by intermittent forward and reverse rotation; the ball milling is performed for 20 to 60 minutes, followed by a 20-minute interval, and then the forward and reverse rotations are alternated for ball milling. The rotation speed of the ball mill is 300 to 350 r / min, and the ball milling time is 5 to 10 hours. Step S 213 The ball mill jar is placed on a ball mill and high-energy ball milling is carried out in an intermittent forward and reverse alternating rotation mode; the ball milling is performed for 30~60 minutes, with a 15-minute interval, and then the forward and reverse alternating ball milling is performed. The rotation speed of the ball mill is 400~600 r / min, and the ball milling time is 50~70 hours. Step S 214 : Let the ball mill jar stand in an inert gas atmosphere for 24 hours, and then turn on the ball mill jar for passivation. The passivation time shall not be less than 24 hours. Step S 215 Remove the ball mill jar and add industrial anhydrous ethanol ball milling media into the ball mill jar according to the volume ratio of powder to anhydrous ethanol of 1:

2. Place it on the ball mill and ball mill at low speed and low energy for 2 hours. The rotation speed of the ball mill is 150~200 r / min, until the ball milled powder is in the form of slurry. Step S 216 Place the ball mill jar in a vacuum drying oven at 50~80℃ and dry for 10 hours; place the ball mill jar on a ball mill and ball mill at a low speed and low energy of 150~200 r / min for 1 hour to break up and separate the powder inside the jar and on the grinding balls. Step S 217 The high-entropy alloy powder was removed from the grinding jar and placed in an agate bowl to fully grind and break up the agglomerated powder. Then, the high-entropy alloy powder was placed back into the agate grinding jar, and Al2O3 ceramic particles of 10-50 nm were added according to the specified ratio. The agate grinding jar was placed on a ball mill and ball milled using a wet grinding method. Zirconia grinding balls were added at a ball-to-material ratio of (8-15):1, and stearic acid grinding media were added at 1-1.5% of the powder mass. Polyvinyl butyral resin (PVB) was added at 2 wt% of the total high-entropy alloy powder mass. The ball mill rotation speed was 150-300 r / min, and the grinding time was 10-40 h. Step S 218 Place the agate ball milling jar in a vacuum drying oven at 50~80℃ and dry for 12 hours; Step S 219 Place the agate ball mill jar on a ball mill and ball mill at a low speed and low energy of 150~200 r / min for 1 hour; take out the ground powder and place it in an agate round bowl for grinding, crushing, sieving, and packaging to obtain nano-level high-entropy alloy repair powder. Step S 22 Add nano-sized high-entropy alloy repair powder into methyl ketone solvent in portions according to a ratio of 10~20g / L. Stir for 10~20min at a stirring speed of 350r / min and a temperature of 30~70℃ to fully mix and form a viscous repair suspension. Step S3: Place the high-entropy alloy workpiece in a viscous repair suspension and disperse it under ultrasonic action for 10-30 minutes to allow the viscous repair suspension to fully penetrate and fill the processing defects of the high-entropy alloy workpiece. Step S4: Dry the high-entropy alloy workpiece from step S3 and place it in an SPS sintering furnace for diffusion and solidification to obtain the repaired workpiece; the sintering process adopts the melt infiltration process, wherein the sintering temperature is 500~600℃, the sintering pressure is 20~50MPa, the holding time is 1~3min, and the melt infiltration pressure is 0.5~2MPa. Step S5: Perform defect inspection on the repaired workpiece. If it fails, repeat steps S3 and S4 above. Step S6: Perform laser surface cladding on the workpiece to improve the repair quality; the specific cladding steps are as follows: Step S 61 A model of the cladding zone is created by scanning the repaired workpiece using modeling software. Step S 62 Import the cladding zone model into the post-processing software to generate the scanning path of the cladding zone; Step S 63 The workpiece surface is preheated, coated with powder, and laser-coated according to a predetermined path. Step S 64 The process involves grinding, polishing, and etching the cladding workpieces, observing the surface morphology of the workpieces, and selecting qualified repaired workpieces.

2. The repair method for high-entropy alloy workpieces according to claim 1, characterized in that, In step S1, the sintering temperature is 800~900℃, the sintering pressure is 20~70MPa, the holding time is 5~10min, the heating rate is 10~30℃ / min, and the vacuum degree is 1×10 -3 Pa.

3. The repair method for high-entropy alloy workpieces according to claim 1, characterized in that, In step S1, machining is one or a combination of turning, milling, and grinding; the surface roughness of the high-entropy alloy workpiece is ≤ Ra1.

6.

4. The repair method for high-entropy alloy workpieces according to claim 1, characterized in that, Step S1 or Step S 211 The medium-high entropy alloy powder is an AlCoCrFeNi alloy powder, and the mass percentages of its components are: 22.88 wt.% Co, 20.61 wt.% Cr, 22.03 wt.% Fe, 23.37 wt.% Ni, 11.09 wt.% Al, 0.0127 wt.% O, 0.0062 wt.% N, with the balance being unavoidable impurities.

5. The repair method for high-entropy alloy workpieces according to claim 1, characterized in that, Step S 63 The substrate for laser cladding is preheated to 300℃; the cladding powder is transferred to the nozzle through the central flow channel and sprayed along the scanning path; the laser spot diameter is 80~100μm, the power is 250~400W, the scanning speed is 800~1400mm / s, the line spacing is 0.15~0.20mm, and the sintered layer thickness is 0.03~0.05mm.

6. The repair method for high-entropy alloy workpieces according to claim 5, characterized in that, The central flow channel of the nozzle is a metal powder flow channel, and the annular flow channel set at 5° to 8° with the metal powder flow channel is a protective gas flow channel; wherein, the protective gas is one or a combination of nitrogen, carbon dioxide, and argon; the cladding powder is TiC or SiC ceramic powder.

Citation Information

Patent Citations

  • High-strength high-toughness ultrafine-grained high-entropy alloy and preparation method thereof

    CN104372230A

  • Repairing material for repairing gas turbine blade and repairing method thereof

    CN114669738A

  • Nano-alumina-coated reinforced refractory high-entropy metal ceramic composite powder and preparation method thereof

    CN116460291A